The Effectiveness Of Cognitive Behavior Therapy In Reducing Loneliness In Adolescents At Khusnul Yaqin Orphanage - Ayuningtyas, Aisha Indah; Fimansyah, Anugrah Akbar; Sentari, Kristin Bayu; Fadiya, Naila Safa; Nursheiliawati, Rieke; Utami, Lufiana Harnany (International Conference on Sustainable Health Promotion, 2023)
A high level of loneliness in orphanage adolescents can hurt their psychological and physical health, such as suffering from depression and physiological aging. This study aims to determine the effectiveness of cognitive behavior therapy (CBT) in reducing feelings of loneliness in adolescents from the Khusnul Yaqin orphanage. The research design used in this study was a one-group pretest-posttest design and involved 10 orphanage youth as subjects selected by purposive sampling technique. This study used the R-UCLA Loneliness Scale Aggression measuring instrument based on Russell's theory (1982). The test used is the paired sample t-test. The results showed that cognitive behavior therapy (CBT) interventions proved effective in reducing loneliness in orphanage adolescents (p = 0.002 where p < 0.05).